2018
DOI: 10.1016/j.cmet.2018.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Non-leptin System that Defends against Weight Gain in Overfeeding

Abstract: Weight is defended so that increases or decreases in body mass elicit responses that favor restoration of one's previous weight. While much is known about the signals that respond to weight loss and the central role that leptin plays, the lack of experimental systems studying the overfed state has meant little is known about pathways defending against weight gain. We developed a system to study this physiology and found that overfed mice defend against increased weight gain with graded anorexia but, unlike wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 44 publications
3
52
0
Order By: Relevance
“…For example, when rats are fed energy-diluted diets or are treated in ways that elevate their metabolic rate, they respond by increasing food intake to an extent that defends their normal body weight [12]. Conversely, when forced into a positive energy balance by infusion of liquid calories, either by gavage or via implanted gastric tubes, animals compensate by lowering their voluntary intake of food [13][14][15][16][17]. Moreover, voluntary feeding completely stops if the quantity of infused calories is sufficiently high.…”
Section: Between Biological Boundaries: How Do Mammals Maintain a Stamentioning
confidence: 99%
See 4 more Smart Citations
“…For example, when rats are fed energy-diluted diets or are treated in ways that elevate their metabolic rate, they respond by increasing food intake to an extent that defends their normal body weight [12]. Conversely, when forced into a positive energy balance by infusion of liquid calories, either by gavage or via implanted gastric tubes, animals compensate by lowering their voluntary intake of food [13][14][15][16][17]. Moreover, voluntary feeding completely stops if the quantity of infused calories is sufficiently high.…”
Section: Between Biological Boundaries: How Do Mammals Maintain a Stamentioning
confidence: 99%
“…In fact, it was shown that a 20-fold higher dose of leptin than that found within the media was needed to produce the level of hypophagia induced by adipose-conditioned media [71]. Moreover, rodents overfed by infusion of liquid diets through gastric tubing compensate for the weight gain by decreasing their voluntary intake of chow [15,17,77]. This response can be observed in both wild-type and genetically obese rodents [15][16][17].…”
Section: Fractionations Of Fat: the Unidentified Anorexigenic Agent Fmentioning
confidence: 99%
See 3 more Smart Citations